An optimal choice Dai-Liao conjugate gradient algorithm for unconstrained optimization and portfolio selection - Sabi'u, Jamilu; Sulaiman, Ibrahim Mohammed; Kaelo, P.; Malik, Maulana; Kamaruddin, Saadi Ahmad (AIMS mathematics, 2024)
In this research, we propose an optimal choice for the non-negative constant in the Dai-Liao conjugate gradient formula based on the prominent Barzilai-Borwein approach by leveraging the nice features of the Frobenius matrix norm. The global convergence of the new modification is demonstrated using some basic assumptions. Numerical comparisons with similar algorithms show that the new approach is reliable in terms of the number of iterations, computing time, and function evaluations for unconstrained minimization, portfolio selection and image restoration problems.